(untitled) (Praxis Educativa, 2019)
This article provides a contribution to the macrostructural study of Educational Inequality. It is based here, the empirical existence of a "differentiated rationality" between the Basic Cycle and the Oriented Cycle of the middle school both in its national and Buenos Aires jurisdiction, for the period 2001/2015. This differentiated behavior is evident from the analysis of indicators of enrollment and internal efficiency from continuous statistics of the nation al and provincial ministries, and the national population censuses of 2001 and 2010. This finding is interpreted from the critical theoretical methodological contributions of the Sociology of Education. In this case, from the "structural genetic" perspec tive (Bourdieu and Wacquant , 2005). From it, the historical structural behavior of the middle school in the "meta field" of the State is interpreted. It also incorporates the category of "hegemony" (Gramsci, 1967), thus complicating the study of the educat ional system power relationship.